The Implementation Of Criminal Law To The Forester Of Land And Land Combustion In Blora Regency - Solikun Ni'am; Akhmad Khisni; Lathifah Hanim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The problems discussed in this study are how is the enforcement of criminal law against the perpetrators of forest and land burning in Blora Regency, as well as the factors inhibiting the enforcement of criminal law against perpetrators of forest and land burning in Blora Regency and its solutions. The approach method used is normative juridical, descriptive analytical research specifications. The data used is secondary data. Data collection method is a field study. The data analysis method uses qualitative analysis. As a knife for analysis, law enforcement theory, justice theory and legal certainty theory are used. The results showed that criminal law enforcement against perpetrators of forest and land burning in Blora Regency was not running optimally. This is evidenced by the absence of investigative efforts carried out by PPNS and the National Police in the crime of burning forests and land, so that there has never been a case of forest fires that has been resolved through a criminal route. Law enforcement efforts are preferred through preventive measures. The inhibiting factors of criminal law enforcement against forest and land arsonists in Blora Regency are the factors of laws where there is disharmony of laws governing forest and land burning crimes, difficulties in finding perpetrators and witnesses, limited costs in investigating forest crime and land and lack of public awareness. The solution to overcome these obstacles is to make criminal law the last resort in enforcing forest and land burning laws, not continuing forest fire cases to the investigation stage, and conducting socialization to the public about preventing forest and land burning.Keywords: Criminal Law Enforcement; Forest And Land Burning.